If he had been with me / Laura Nowlin. - Nowlin, Laura (Sourcebooks Fire, 2019)
Throughout their childhood Finn and Autumn were inseperable. But one incident in middle school put them in different worlds. Despite her relationship with James, Autumn has always wondered what would have happened if Finn had been with her.